Understanding sustainable purchase intention of smartphone users interface: Evidence from China - Horani, Lara F.; Dong, Liangdong (Frontiers in Psychology, 2023)
In recent decades, the fast development of smartphones has resulted in an enormous mass of e-waste besides a carbon footprint increase. In the face of serious environmental concerns, the manufacture and disposal of smartphones have become a primary customer concern. Environmental concerns are becoming a decisive factor when it comes to purchasing a product. Manufacturers have shifted their focus to product design with sustainable requirements in response to these new customer requirements. With all of the affordable technology manufacturers now may consider customer sustainable requirements. This research aims to examine the relationship between traditional customer requirements, sustainable customer requirements, and sustainable purchase intention for smartphones in china, as well as the mediation effect of sustainable perceived value and the moderation effect of price sensitivity. Customers’ preferences are determined by using an online questionnaire. This research proposed an advanced sustainable purchase intention model by conducting an empirical analysis of the data gathered from 379 questionnaires. To gain a competitive advantage, companies should concentrate on meeting traditional and sustainable requirements more than the product price, according to the findings of the research. And contributes to the segmentation of the eco-friendly smartphone market.